Plankton distribution patterns and the indicative significance of diverse cave wetlands in subtropical karst basin - Guo, Fang; Jiang, Guanghui; Liu, Fan (Frontiers in Environmental Science, 2022)
In subtropical karst area, small wetlands are widely distributed owing to the well-developed karst and the high degree of groundwater- surface water interaction. However, detailed plankton community composition, spatial-temporal dynamics, and its assembly mechanism were rarely discussed. To address these, plankton distribution patterns and its relationship with hydrological conditions and environment gradients were analyzed to discover the biological characteristics of wetlands in a typical karst basin in South China. The results showed that the wetlands were diversity in types due to the hydrogeology background. Water quality evaluation according to major ions analyses showed good results, with significant differences among samples and a poor status when measured by biotic indicator such as Escherichia coli. During high and low-flow condition, a total of 163 and 162 species of phytoplankton, and a total of 62 and 36 species of zooplankton, respectively were observed. The dominant species of phytoplankton communities in low-flow condition metamorphosed from Cyclotella sp. to Navicula sp. and Cocconeis placentula; and Pediastrum simplex to Ankistrodesmus spiralis. The metamorphosis in zooplankton community was from Difflugia globulosa to Strobilidium sp. Comparing with other karst water in different climate regimes, the number of plankton species in the subtropical karst wetland was the highest, which is related to the high and stable water temperature, large karst underground spaces, and frequent interaction between groundwater and surface water. The abundance, biomass and community semblance of plankton increased with an increase in nutrients, precipitating improvement in hydrodynamics and light intensity. This study also suggested that the plankton in karst cave wetlands in subtropical area were characterized by low diversity, attributable to the calcium-rich and weakly alkaline, but poor nutrient status of the water environment, as well as drew attention to the possible functions of wetlands in relation to the quality of connected river.